Effects of different incubation times toward RNA recovery in plasma RNA extraction - Wan Nor Ruddin, Wan Alif Afiq; Mohd Nor, Nurul Yaqin; Ismail, Hamizah; Zainuddin, Norafiza (Biome Scientia Sdn Bhd, 2022)
RNA in plasma samples are known to exist in marginal amount, contributing to difficulties in obtaining favourable RNA results for downstream applications. Thereby, numerous plasma RNA extraction protocols that utilized different solutions were implemented. These protocols are frequently comparable with slight differences in the parameters especially on the incubation time. Hence, this paper will focus on the implications of different incubation periods in plasma RNA extraction protocol to identify the dependency of plasma RNA towards incubation times and how they are affected. Plasma RNA were extracted using miRNeasy Serum/Plasma (Qiagen, Germany). To test the effects of incubation time, the RNA extractions were repeated with reduced and extended incubation periods for several minutes gaps at certain steps, for instance, the extractions were done distinctly with three- (reduced), five- (default) and seven- minutes (extended) incubation period after TRIzol reagent addition and the results were compared. Our results demonstrated positive correlations when the incubation times were increased during sample homogenization and RNA precipitation, yielding around 14.30 ng/μL to 17.50 ng/μL, and 13.43 ng/μL to 20.05 ng/μL respectively compared to the average of 10.37 ng/μL on default duration. Generally, longer period of incubation might allow sufficient RNA recovery to occur. Steps like sample homogenization and RNA precipitation require longer incubation time for complete RNA recovery since plasma RNA are considerably dignified than DNA or other RNAs due to their low level and encapsulated within exosomes. Thus, the incubation time within extraction protocol play an important role for efficient plasma RNA recovery.